Risk Assessment of Goods Sorting Activities in Cold Storage Using Job Safety Analysis (Case Study: Logistics Warehouse, Japan) - Yelita Anggiane Iskandar; Bathara Hananta Ramdhan; Lana Salsabila Muhyi; Rahma Alia Azzahro; Winda Septiana (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2026)
Goods sorting (shiwake) activities at the Shimohana Logistics warehouse in Atsugi, Japan, constitute the focus of this study, which aims to identify potential hazards, assess risk levels, and evaluate the implementation of occupational health, safety, security, and environmental (HSSE) practices. A qualitative descriptive approach was employed through direct observations, interviews, and documentation review, with risk analysis conducted using the Job Safety Analysis (JSA) method and risk assessment based on likelihood and severity parameters aggregated using the geometric mean. The results identified 11 potential hazards encompassing mechanical, ergonomic, and environmental aspects, with risk levels ranging from low to extreme. The highest risk (RR = 16) was associated with forklift traffic interactions in the sorting area, while other high risks (RR = 9-12) were linked to non-ergonomic postures, repetitive manual handling, and prolonged exposure to cold temperatures. Moderate and low risks were found in manual trolley usage, unstable stacking conditions, and exposure to scanner lighting. The application of JSA integrated with HSSE principles enables a structured and systematic approach to hazard identification and risk control. The findings indicate that, despite efficient warehouse operations, significant risks remain in sorting activities, particularly in worker–equipment interactions and cold environment exposure. Therefore, targeted mitigation strategies including segregation of forklift and pedestrian pathways, ergonomic improvements, workload regulation, and the use of cold-resistant personal protective equipment are recommended. These measures are expected to enhance workplace safety, reduce accident risks, and support continuous improvement toward a safer and more sustainable warehouse operation aligned with the zero-accident principle.